2002
DOI: 10.1002/mds.10280
|View full text |Cite
|
Sign up to set email alerts
|

Memory and executive function impairment predict dementia in Parkinson's disease

Abstract: We analyzed the association of neuropsychological test impairment at baseline with the development of dementia in idiopathic Parkinson's disease (PD) patients. A cohort of nondemented PD patients from northern Manhattan, NY was followed annually with neurological and neuropsychological evaluations. The neuropsychological battery included tests of verbal and nonverbal memory, orientation, visuospatial ability, language, and abstract reasoning. The association of baseline neuropsychological tests scores with inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
173
4
6

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(199 citation statements)
references
References 39 publications
16
173
4
6
Order By: Relevance
“…It was observed that a higher schooling level was associated with a reduced risk in cognitive impairment, confirming earlier studies with PD patients 6,19 . Nevertheless longitudinal studies are required to elucidate the aspect of the "protective effect" of a higher level of formal education on the cognition of PD patients 19 .…”
Section: Clinical Aspects and Cognitive Declinesupporting
confidence: 87%
See 2 more Smart Citations
“…It was observed that a higher schooling level was associated with a reduced risk in cognitive impairment, confirming earlier studies with PD patients 6,19 . Nevertheless longitudinal studies are required to elucidate the aspect of the "protective effect" of a higher level of formal education on the cognition of PD patients 19 .…”
Section: Clinical Aspects and Cognitive Declinesupporting
confidence: 87%
“…various references can be found in the literature with respect to a relationship between dementia and the score obtained on the Unified Parkinson Disease Rating Scale, especially in the sub-score indicating predominantly dopaminergic dysfunction 6,8 .…”
Section: Dementia and Mild Cognitive Impairment In Pdmentioning
confidence: 99%
See 1 more Smart Citation
“…Longitudinal studies are crucial in terms of better describing these deficits and their significance for long-term prognosis. However, historically such studies have failed to give a consistent picture, implicating a number of different neuropsychological deficits as predictors of dementia in PD, including executive deficits, [18][19][20] poor verbal fluency, [20,21] visuospatial dysfunction, [20] and language and memory deficits [19,22]. This inconsistency is likely to relate to important methodological differences between these studies including the nature of the cohorts (hospital versus community-based), disease stage of patients included, and the choice of neuropsychological assessments.…”
Section: What Can Cause the Cognitive Deficits In Pd?mentioning
confidence: 99%
“…Уже на этапе УКР при нейропсихологическом тестировании не менее чем у 50% пациентов выявляются нарушения зрительно-про-странственных функций и памяти [88,91]. Раннее нару-шение исполнительных функций и памяти является фак-тором риска развития деменции при БП [86,[92][93][94][95]. Ког-нитивный дефект при БП традиционно обозначают как подкорковый или лобно-подкорковый, в отличие от кор-кового дефекта при болезни Альцгеймера (БА) [96].…”
unclassified